PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN KONTEKSTUAL SETTING KOOPERATIF TIPE TWO STAY TWO STRAY SUB POKOK BAHASAN PERSEGI PANJANG DAN PERSEGI KELAS VII SMP - Fawaid, Ahmad Rif’an; Trapsilasiwi, Dinawati; Sri Lestari, Nurcholif Diah (KadikmA, 2013)
Abstract. The research purpose is to know the process and result of development of mathematics learning instruments based on contextual teaching and learning by setting of cooperative learning two stay two stray for rectangle and square topic at seventh grade of junior high school. Learning instruments development model refers to 4D Thiagarajan models which has 4 steps namely define, design, develop, and disseminate. This research has three products namely lesson plan, worksheet, and evaluation test. Based on validation process and tryout, it can be concluded that the learning instruments had fullfiled with validity, practice, and effective criteria. Key Words : 4D Thiagarajan models, contextual teaching and learning, cooperative learning two stay two stray, rectangle and square